DIAGNOSTICS AND TREATMENT OF DIOCTOPHYMOSIS IN DOGS - Shabdarbaeva G.; Balgimbayeva A.; Zhanteliyeva Laura; Ibazhanova A.; Uğur USLU; Khussainov Damir (Scientific Journal of Pedagogy and Economics, 2020)
This article includes materials on the rare disease in domestic and wild carnivores, dioctophimosis, caused by a helminth from the group of aphasmidia nematodes, Dioctophyme renale, which is parasitic in the kidneys, recently registered in veterinary clinics in Almaty. The disease has important social significance - a person is susceptible to it, the infection of which occurs when raw fish is eaten. In Almaty, according to the statistics of veterinary clinics in recent years (2018-2019), 17 cases of dioctophimosis in dogs have been registered, that is up to 0.3% of the number of dogs examined for helminthiases. The appearance of this disease, which is relatively new for our region, can have a significant impact on the epizootiological and epidemiological situation. The results of in vivo laboratory diagnosis of dioctophimosis in dogs by ovoscopic methods are presented, with the provision of microphotos of the parasite eggs; methods of instrumental diagnostics - ultrasound examination (ultrasound) of the kidneys with the provision of photos proving the presence of a parasite in the renal pelvis. Since the only treatment for dioctophimosis is surgery and extraction of dioctophyma from the affected organ (kidney), our own original materials are presented for a step by step surgical intervention to extract helminth from the kidneys of dogs and treat animals. The condition of the operated animals is satisfactory, the prognosis for surgery is favorable.